Pengaruh Model Direct Instruction Di Kalangan Siswa Berkemampuan Akademik Berbeda Terhadap Kemampuan Berpikir Kritis Pada Pembelajaran Biologi - M. Danil (Jurnal Ilmiah Wahana Pendidikan, 2022)
Selection of the right learning model will provide a meaningful learning experience for students so as to maximize students' cognitive learning outcomes. The purpose of this study was to determine the effect of the Problem Based Learning (PBL) model among students with different academic abilities on cognitive learning outcomes in biology learning. This study used a quasi-experimental research design. The number of research samples was 202 class X students consisting of 4 upper academic ability classes and 4 lower academic ability classes taken from 5 schools namely Bireuen 3 Public High School, Peusangan 1 Public High School, Gandapura 1 Public High School, Siblah Krueng 1 Peusangan High School and High School Country 1 Term. Determination of the sample is done by random sampling technique. Critical thinking skills data collection is done by giving an essay test. The research data were analyzed using qualitative descriptive statistics to describe the ability to think critically and statistical inferential analysis of covariates (Anakova) with a significance level of 5% which was used to test the hypothesis. Anakova test results show that in the PBL model and academic ability on students' cognitive learning outcomes it is known that the p-level value (0.000) <α (0.05) with a significance of 0.000 and 0.000. So it can be concluded that the PBL model has an effect on cognitive learning outcomes in biology learning